Spirituality-based environmental literacy among prospective biology teacher in Indonesia: Analysis based on gender, accreditation, and semester-level aspects - H. Husamah; Abdulkadir Rahardjanto; Samsun Hadi; Nurdiyah Lestari; Muh. Khaerul Ummah BK (University of Muhammadiyah Malang, 2023)
Spirituality-based environmental literacy (SEL) influences ecological knowledge, environmental expectations, cognitive abilities, and environmental-related behavior. In this regard, this research aims to determine SEL among prospective biology teacher throughout Indonesia. This study included a cross-sectional survey. The target respondents are students of education study programs in the field of biology who come from various institutions in Indonesia. Gender aspects, study program accreditation status, and semester-level are positioned as respondent characteristics whose impact on environmental literacy is analyzed. The sample size is 632 students. The data collection instrument used was the ELIS. The data collection process is carried out online. Data was analyzed using SPSS. We discuss the results of different tests based on gender, different tests based on accreditation, and different tests based on semester-level. This research provides unique results. Women have higher levels of SEL than men. There are significant differences between men and women in terms of environmental literacy, although references do not always support this. Accreditation status does not support differences in SEL levels. Furthermore, the semester-level (final semester) has a higher SEL, but that is only in the knowledge aspect. On that basis, we suggest several aspects to consider in future research.